2018
DOI: 10.1111/liv.13649
|View full text |Cite
|
Sign up to set email alerts
|

Hypergammaglobulinemia is a strong predictor of disease progression, hepatocellular carcinoma, and death in patients with compensated cirrhosis

Abstract: Hypergammaglobulinemia identifies C-P class A cirrhotic patients at higher risk of disease progression, HCC development and death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…It was reported that globulin is positively associate with mortality in patients with cirrhosis [31]. Serum gamma-globulin ≥18 g/L is a significant predictor of disease progression, tumor development and death for cirrhotic patients [32]. INR is used to assess bleeding risk and prognosis in cirrhosis, and end-stage liver disease score that integrates INR has the ability to prioritize patients for liver transplantation [33].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that globulin is positively associate with mortality in patients with cirrhosis [31]. Serum gamma-globulin ≥18 g/L is a significant predictor of disease progression, tumor development and death for cirrhotic patients [32]. INR is used to assess bleeding risk and prognosis in cirrhosis, and end-stage liver disease score that integrates INR has the ability to prioritize patients for liver transplantation [33].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Cacciola et al studied the role of serum gamma globulins in relation to the clinical outcome in cirrhotic patients [ 19 ]. They proved that hypergammaglobulinemia is a strong predictor of disease progression, hepatocellular carcinoma and death in patients with cirrhosis, and that hypergammaglobulinemia may help identify the CTP class A cirrhotics with a poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis by imaging in the majority of cases removes the luxury of using traditional immunohistochemistry (IHC), or next-generation sequencing used to identify useful biomarkers like Her2 in breast cancer and MMR in colon cancer. As detailed in the table 1, biomarkers can be serum/blood-based testing [9][10][11][12][13][14][15][16][17] , genetic data (IHC or sequencing,) [16][17][18][19][20][21][22][23] , mutations in circulating tumor cells (CTC) [24] , or treatment specific (sorafenib [25,26] ,TARE [27] or SBRT [28] ). Most of these markers did not reach the clinical practice as of today.…”
Section: Biomarkers In Clinical Practicementioning
confidence: 99%